2016
DOI: 10.5966/sctm.2015-0161
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Determines the Immunophenotypic Profile and Functional Characteristics of Human Mesenchymal Stem Cells From Adipose Tissue

Abstract: Adipose tissue is a major source of mesenchymal stem cells (MSCs), which possess a variety of properties that make them ideal candidates for regenerative and immunomodulatory therapies. Here, we compared the immunophenotypic profile of human adipose-derived stem cells (hASCs) from lean and obese individuals, and explored its relationship with the apparent altered plasticity of hASCs. We also hypothesized that persistent hypoxia treatment of cultured hASCs may be necessary but not sufficient to drive significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
112
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(126 citation statements)
references
References 49 publications
11
112
0
3
Order By: Relevance
“…However, it is also reported that ASCs isolated from the subcutaneous abdominal adipose tissue of obese patients demonstrated an increased ability in invasion associated with the expression of calpain‐4, calpastatin and MMP‐15 . The immunophenotypic profile and the migration pattern were compared between human lean and obese ASCs . Relative to lean ASCs, obese ASCs showed an increased basal migration capacity, correlating with a higher expression of human leukocyte antigen (HLA)‐II .…”
Section: Dysfunction Of Adipose‐derived Mesenchymal Stem Cells In Obementioning
confidence: 99%
See 2 more Smart Citations
“…However, it is also reported that ASCs isolated from the subcutaneous abdominal adipose tissue of obese patients demonstrated an increased ability in invasion associated with the expression of calpain‐4, calpastatin and MMP‐15 . The immunophenotypic profile and the migration pattern were compared between human lean and obese ASCs . Relative to lean ASCs, obese ASCs showed an increased basal migration capacity, correlating with a higher expression of human leukocyte antigen (HLA)‐II .…”
Section: Dysfunction Of Adipose‐derived Mesenchymal Stem Cells In Obementioning
confidence: 99%
“…The immunophenotypic profile and the migration pattern were compared between human lean and obese ASCs . Relative to lean ASCs, obese ASCs showed an increased basal migration capacity, correlating with a higher expression of human leukocyte antigen (HLA)‐II . Yet, low oxygen tension increased migration of lean but not obese ASCs, which correlated with an altered CD36 and CD49b immunophenotypic profile .…”
Section: Dysfunction Of Adipose‐derived Mesenchymal Stem Cells In Obementioning
confidence: 99%
See 1 more Smart Citation
“…AT also serves as a novel source of adult stem cells, termed adipose stem cells (ASCs), which have great potential for therapeutic applications [5]. However, we and others have shown that the environmental niche in which ASCs reside has a profound impact on their functional properties [6], [7], [8].…”
Section: Introductionmentioning
confidence: 99%
“…Subcutaneous adipose tissue from obese patients has a diminished reservoir of functionally active stem cells [85]. Moreover, metabolism and maturation of APCs are arrested in an obese environment [17], and their ability to migrate or invade a tissue is impaired [86, 87]. Mechanistically, obesity causes a short circuit in the stemness gene network [88], promoting an imbalance in metabolism and a reduction in stemness properties [89].…”
Section: Stem Cell Behavior In Different Diseasesmentioning
confidence: 99%